Kad Hai Raya - Abdullah, Ahmad Kamal; -, Pon Mariam; -, Ainin Akmar; -, Ainul Azam; -, Ainil Umar; -, Ainal Adnin (Nil, 1989)
Kad ucapan hari raya yang diutuskan kepada Profesor Diraja Ungku Abdul Aziz daripada Ahmad Kamal Abdullah, Pon Mariam, Ainin Akmar, Ainul Azam, Ainil Umar dan Ainal Adnin